Finite-Time Distributed Energy-to-Peak Control for Uncertain Multiagent Systems - Qu Chenggang; Cao Xibin; Hamid Reza Karimi; Zhang Zhuo; Zhang Zexu (Abstract and Applied Analysis)
This paper investigates the finite-time distributed L2–L∞ consensus control problem of multiagent systems with parameter uncertainties. The relative states of neighboring agents are used to construct the control law and some agents know their own states. By substituting the control input into multiagent systems, an augmented closed-loop system is obtained. Then, we analyze its finite-time boundedness (FTB) and finite-time L2–L∞ performance. A sufficient condition for the existence of the designed controller is given with the form of linear matrix inequalities (LMIs). Finally, simulation results are described.